2005
DOI: 10.1002/dmrr.586
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E and C supplementation combined with oral antidiabetic therapy on the endothelial dysfunction in the neonatally streptozotocin injected diabetic rat

Abstract: Apparently, a selective endothelial dysfunction accompanies the imbalance in oxidant/antioxidant status in the type-2 diabetes model of rat and gliclazide and/or vitamin supplementation improves the impairment in diabetic vasculature. However, vitamin supplementation triggers oxidative stress in normal aortic tissue, thereby, leads to endothelial dysfunction; indicating that nutritional extra-supplementation of antioxidant vitamins isn't advisable for normal subjects, although it's beneficial in disease status. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 46 publications
4
13
1
Order By: Relevance
“…These findings according with our study that inhibition effects of vit E on Oxidative stress produced in diabetes patients. Alper et al [28] showed that there is an imbalance in oxidant/antioxidant status in the type-2 diabetes model of rat and vitamin supplementation improves the impairment in diabetic vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…These findings according with our study that inhibition effects of vit E on Oxidative stress produced in diabetes patients. Alper et al [28] showed that there is an imbalance in oxidant/antioxidant status in the type-2 diabetes model of rat and vitamin supplementation improves the impairment in diabetic vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 However, some studies reported that antioxidant vitamin supplementation may lead to endothelium dysfunction in both diabetic and normal animals. 42,43 Proposed mechanisms for this observation include prooxidant effects of vitamin E on vitamin C in the presence of NO and/or de novo synthesis of vasoconstrictive prostanoids. 44 Differing levels of vitamin E and C prior to repletion may also play a role.…”
Section: Animal Studiesmentioning
confidence: 99%
“…It is frequently co-administered with vitamin C because its oxidized form is regenerated by vitamin C. Vitamin E and C supplementation improves markers of oxidative stress and endothelium-dependent vasodilation in experimental diabetic models (4245). Acute administration of vitamin E has generally been shown to improve endothelial dependent brachial artery vasodilatation in both type 1 and 2 diabetes (46).…”
Section: Therapeutic Interventions That Modify Oxidative Stressmentioning
confidence: 99%